Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

Class 10 RD Sharma Solutions- Chapter 2 Polynomials – Exercise 2.1 | Set 1

  • Last Updated : 02 Feb, 2021

Question 1. Find the zeros of each of the following quadratic polynomials and verify the relationship between the zeros and their coefficients:

(i) f(x) = x2 – 2x – 8

Solution: 

Given that,

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

f(x) = x2 – 2x – 8



To find the zeros of the equation, put f(x) = 0

= x2 – 2x – 8 = 0

= x2 – 4x + 2x – 8 = 0

= x(x – 4) + 2(x – 4) = 0

= (x – 4)(x + 2) = 0

x = 4 and x = -2

Hence, the zeros of the quadratic equation are 4 and -2.

Now, Verification

As we know that,

Sum of zeros = – coefficient of x / coefficient of x^2

4 + (-2)= – (-2) / 1

2 = 2

Product of roots = constant / coefficient of x^2

4 x (-2) = (-8) / 1

-8 = -8

Hence the relationship between zeros and their coefficients are verified.

(ii) g(s) = 4s2 – 4s + 1

Solution: 

Given that,



g(s) = 4s2 – 4s + 1

To find the zeros of the equation, put g(s) = 0

= 4s2 – 4s + 1 = 0

= 4s2 – 2s – 2s + 1= 0

= 2s(2s – 1) – (2s – 1) = 0

= (2s – 1)(2s – 1) = 0

s = 1/2 and s = 1/2

Hence, the zeros of the quadratic equation are 1/2 and 1/2.

Now, Verification

As we know that,

Sum of zeros = – coefficient of s / coefficient of s2

1/2 + 1/2 = – (-4) / 4

1 = 1

Product of roots = constant / coefficient of s2

1/2 x 1/2 = 1/4

1/4 = 1/4

Hence the relationship between zeros and their coefficients are verified.

(iii) h(t)=t2 – 15

Solution: 

Given that,

h(t) = t2 – 15 = t2 +(0)t – 15



To find the zeros of the equation, put h(t) = 0

= t2 – 15 = 0

= (t + √15)(t – √15)= 0

t = √15 and t = -√15

Hence, the zeros of the quadratic equation are √15 and -√15.

Now, Verification

As we know that,

Sum of zeros = – coefficient of t / coefficient of t2

√15 + (-√15) = – (0) / 1

0 = 0

Product of roots = constant / coefficient of t2

√15 x (-√15) = -15/1

-15 = -15

Hence the relationship between zeros and their coefficients are verified.

(iv) f(x) = 6x2 – 3 – 7x

Solution: 

Given that,

f(x) = 6x2 – 3 – 7x

To find the zeros of the equation, we put f(x) = 0

= 6x2 – 3 – 7x = 0

= 6x2 – 9x + 2x – 3 = 0

= 3x(2x – 3) + 1(2x – 3) = 0

= (2x – 3)(3x + 1) = 0

x = 3/2 and x = -1/3

Hence, the zeros of the quadratic equation are 3/2 and -1/3.

Now, Verification

As we know that,

Sum of zeros = – coefficient of x / coefficient of x2

3/2 + (-1/3) = – (-7) / 6

7/6 = 7/6

Product of roots = constant / coefficient of x2



3/2 x (-1/3) = (-3) / 6

-1/2 = -1/2

Hence the relationship between zeros and their coefficients are verified.

(v) p(x) = x2 + 2√2x – 6

Solution: 

Given that,

p(x) = x2 + 2√2x – 6

To find the zeros of the equation, put p(x) = 0

= x2 + 2√2x – 6 = 0

= x2 + 3√2x – √2x – 6 = 0

= x(x + 3√2) – √2 (x + 3√2) = 0

= (x – √2)(x + 3√2) = 0

x = √2 and x = -3√2

Hence, the zeros of the quadratic equation are √2 and -3√2.

Now, Verification

As we know that,

Sum of zeros = – coefficient of x / coefficient of x2

√2 + (-3√2) = – (2√2) / 1

-2√2 = -2√2

Product of roots = constant / coefficient of x2

√2 x (-3√2) = (-6) / 2√2

-3 x 2 = -6/1

-6 = -6

Hence the relationship between zeros and their coefficients are verified.

(vi) q(x)=√3x2 + 10x + 7√3

Solution: 

Given that,

q(x) = √3x2 + 10x + 7√3

To find the zeros of the equation, put q(x) = 0

= √3x2 + 10x + 7√3 = 0

= √3x2 + 3x +7x + 7√3x = 0

= √3x(x + √3) + 7 (x + √3) = 0

= (x + √3)(√3x + 7) = 0

x = -√3 and x = -7/√3

Hence, the zeros of the quadratic equation are -√3 and -7/√3.

Now, Verification

As we know that,

Sum of zeros = – coefficient of x / coefficient of x2

-√3 + (-7/√3) = – (10) /√3

(-3-7)/ √3 = -10/√3

-10/ √3 = -10/√3

Product of roots = constant / coefficient of x2



(-√3) x (-7/√3) = (7√3) / √3

7 = 7

Hence the relationship between zeros and their coefficients are verified.

(vii) f(x) = x2 – (√3 + 1)x + √3

Solution: 

Given that,

f(x) = x2 – (√3 + 1)x + √3

To find the zeros of the equation, put f(x) = 0

= x2 – (√3 + 1)x + √3 = 0

= x2 – √3x – x + √3 = 0

= x(x – √3) – 1 (x – √3) = 0

= (x – √3)(x – 1) = 0

x = √3 and x = 1

Hence, the zeros of the quadratic equation are √3 and 1.

Now, Verification

Sum of zeros = – coefficient of x / coefficient of x2

√3 + 1 = – (-(√3 +1)) / 1

√3 + 1 = √3 +1

Product of roots = constant / coefficient of x2

1 x √3 = √3 / 1

√3 = √3

Hence the relationship between zeros and their coefficients are verified.

(viii) g(x) = a(x2+1)–x(a2+1)

Solution: 

Given that,

g(x) = a(x2+1)–x(a2+1)

To find the zeros of the equation put g(x) = 0

= a(x2+1)–x(a2+1) = 0

= ax2 + a − a2x – x = 0

= ax2 − a2x – x + a = 0

= ax(x − a) − 1(x – a) = 0

= (x – a)(ax – 1) = 0

x = a and x = 1/a

Hence, the zeros of the quadratic equation are a and 1/a.

Now, Verification :

As we know that,

Sum of zeros = – coefficient of x / coefficient of x2

a + 1/a = – (-(a2 + 1)) / a

(a^2 + 1)/a = (a2 + 1)/a

Product of roots = constant / coefficient of x2

a x 1/a = a / a

1 = 1

Hence the relationship between zeros and their coefficients are verified.

(ix) h(s) = 2s2 – (1 + 2√2)s + √2

Solution: 

Given that,

h(s) = 2s2 – (1 + 2√2)s + √2

To find the zeros of the equation put h(s) = 0

= 2s2 – (1 + 2√2)s + √2 = 0

= 2s2 – 2√2s – s + √2 = 0

= 2s(s – √2) -1(s – √2) = 0

= (2s – 1)(s – √2) = 0

x = √2 and x = 1/2



Hence, the zeros of the quadratic equation are √3 and 1.

Now, Verification

As we know that,

Sum of zeros = – coefficient of s / coefficient of s2

√2 + 1/2 = – (-(1 + 2√2)) / 2

(2√2 + 1)/2 = (2√2 +1)/2

Product of roots = constant / coefficient of s2

1/2 x √2 = √2 / 2

√2 / 2 = √2 / 2

Hence the relationship between zeros and their coefficients are verified.

(x) f(v) = v2 + 4√3v – 15

Solution: 

Given that,

f(v) = v2 + 4√3v – 15

To find the zeros of the equation put f(v) = 0

= v2 + 4√3v – 15 = 0

= v2 + 5√3v – √3v – 15 = 0

= v(v + 5√3) – √3 (v + 5√3) = 0

= (v – √3)(v + 5√3) = 0

v = √3 and v = -5√3

Hence, the zeros of the quadratic equation are √3 and -5√3.

Now, for verification

Sum of zeros = – coefficient of v / coefficient of v2

√3 + (-5√3) = – (4√3) / 1

-4√3 = -4√3

Product of roots = constant / coefficient of v2

√3 x (-5√3) = (-15) / 1

-5 x 3 = -15

-15 = -15

Hence the relationship between zeros and their coefficients are verified.

(xi) p(y) = y2 + (3√5/2)y – 5

Solution: 

Given that,

p(y) = y2 + (3√5/2)y – 5

To find the zeros of the equation put f(v) = 0

= y2 + (3√5/2)y – 5 = 0

= y2 – √5/2 y + 2√5y – 5 = 0

= y(y – √5/2) + 2√5 (y – √5/2) = 0

= (y + 2√5)(y – √5/2) = 0

This gives us 2 zeros,

y = √5/2 and y = -2√5

Hence, the zeros of the quadratic equation are √5/2 and -2√5.

Now, Verification

As we know that,

Sum of zeros = – coefficient of y / coefficient of y2

√5/2 + (-2√5) = – (3√5/2) / 1

-3√5/2 = -3√5/2

Product of roots = constant / coefficient of y2

√5/2 x (-2√5) = (-5) / 1

– (√5)2 = -5

-5 = -5

Hence the relationship between zeros and their coefficients are verified.

(xii) q(y) = 7y2 – (11/3)y – 2/3

Solution: 

Given that,

q(y) = 7y2 – (11/3)y – 2/3

To find the zeros of the equation put q(y) = 0

= 7y2 – (11/3)y – 2/3 = 0

= (21y2 – 11y -2)/3 = 0

= 21y2 – 11y – 2 = 0

= 21y2 – 14y + 3y – 2 = 0

= 7y(3y – 2) – 1(3y + 2) = 0

= (3y – 2)(7y + 1) = 0



y = 2/3 and y = -1/7

Hence, the zeros of the quadratic equation are 2/3 and -1/7.

Now, Verification

As we know that,

Sum of zeros = – coefficient of y / coefficient of y2

2/3 + (-1/7) = – (-11/3) / 7

-11/21 = -11/21

Product of roots = constant / coefficient of y2

2/3 x (-1/7) = (-2/3) / 7

– 2/21 = -2/21

Hence the relationship between zeros and their coefficients are verified.

Question 2. For each of the following, find a quadratic polynomial whose sum and product respectively of the zeros are as given. Also, find the zeros of these polynomials by factorization.

(i) -8/3, 4/3

Solution: 

As we know that the quadratic polynomial formed for the given sum and product of zeros is given by : f(x) = x2 + -(sum of zeros) x + (product of roots)

The sum of zeros = -8/3 and

Product of zero = 4/3

Therefore,

Required polynomial f(x) is,

= x2 – (-8/3)x + (4/3)

= x2 + 8/3x + (4/3)

To find the zeros we put f(x) = 0

= x2 + 8/3x + (4/3) = 0

= 3x2 + 8x + 4 = 0

= 3x2 + 6x + 2x + 4 = 0

= 3x(x + 2) + 2(x + 2) = 0

= (x + 2) (3x + 2) = 0

= (x + 2) = 0 and, or (3x + 2) = 0

Hence, the two zeros are -2 and -2/3.

(ii) 21/8, 5/16

Solution: 

As we know that the quadratic polynomial formed for the given sum and product of zeros is given by : f(x) = x2 + -(sum of zeros) x + (product of roots)

The sum of zeros = 21/8 and

Product of zero = 5/16

Therefore,

The required polynomial f(x) is,

= x2 – (21/8)x + (5/16)

= x2 – 21/8x + 5/16

To find the zeros we put f(x) = 0

= x2 – 21/8x + 5/16 = 0

= 16x2 – 42x + 5 = 0

= 16x2 – 40x – 2x + 5 = 0

= 8x(2x – 5) – 1(2x – 5) = 0

= (2x – 5) (8x – 1) = 0

= (2x – 5) = 0 and, or (8x – 1) = 0

Hence, the two zeros are 5/2 and 1/8.

(iii) -2√3, -9

Solution: 

As we know that the quadratic polynomial formed for the given sum and product of zeros is given by : f(x) = x2 + -(sum of zeros) x + (product of roots)

The sum of zeros = -2√3 and

Product of zero = -9

Therefore,

The required polynomial f(x) is,

= x2 – (-2√3)x + (-9)

= x2 + 2√3x – 9

To find the zeros we put f(x) = 0

= x2 + 2√3x – 9 = 0

= x2 + 3√3x – √3x – 9 = 0

= x(x + 3√3) – √3(x + 3√3) = 0

= (x + 3√3) (x – √3) = 0

= (x + 3√3) = 0 and, or (x – √3) = 0

Hence, the two zeros are -3√3and √3.

(iv) -3/2√5, -1/2

Solution: 

As we know that the quadratic polynomial formed for the given sum and product of zeros is given by : f(x) = x2 + -(sum of zeros) x + (product of roots)



The sum of zeros = -3/2√5 and

Product of zero = -1/2

Therefore,

The required polynomial f(x) is,

= x2 – (-3/2√5)x + (-1/2)

= x2 + 3/2√5x – 1/2

To find the zeros we put f(x) = 0

= x2 + 3/2√5x – 1/2 = 0

= 2√5x2 + 3x – √5 = 0

= 2√5x2 + 5x – 2x – √5 = 0

= √5x(2x + √5) – 1(2x + √5) = 0

= (2x + √5) (√5x – 1) = 0

= (2x + √5) = 0 and, or (√5x – 1) = 0

Hence, the two zeros are -√5/2 and 1/√5.

Question 3. If α and β are the zeros of the quadratic polynomial f(x) = x2 – 5x + 4, find the value of 1/α + 1/β – 2αβ.

Solution: 

Given that,

α and β are the roots of the quadratic polynomial f(x) where a = 1, b = -5 and c = 4

Using these values we can find,

Sum of the roots = α+β = -b/a = – (-5)/1 = 5,

Product of the roots = αβ = c/a = 4/1 = 4

We have to find 1/α +1/β – 2αβ

= [(α +β)/ αβ] – 2αβ

= (5)/ 4 – 2(4) = 5/4 – 8 = -27/ 4

Question 4. If α and β are the zeros of the quadratic polynomial p(y) = 5y2 – 7y + 1, find the value of 1/α+1/β.

Solution: 

Given that,

α and β are the roots of the quadratic polynomial f(x) where a =5, b = -7 and c = 1,

Using these values we can find,

Sum of the roots = α+β = -b/a = – (-7)/5 = 7/5

Product of the roots = αβ = c/a = 1/5

We have to find 1/α +1/β

= (α +β)/ αβ

= (7/5)/ (1/5) = 7

Question 5. If α and β are the zeros of the quadratic polynomial f(x)=x2 – x – 4, find the value of 1/α+1/β–αβ.

Solution: 

Given that,

α and β are the roots of the quadratic polynomial f(x) where a = 1, b = -1 and c = – 4

So, we can find,

Sum of the roots = α+β = -b/a = – (-1)/1 = 1

Product of the roots = αβ = c/a = -4 /1 = – 4

We have to find, 1/α +1/β – αβ

= [(α +β)/ αβ] – αβ

= [(1)/ (-4)] – (-4) = -1/4 + 4 = 15/ 4

Question 6. If α and β are the zeroes of the quadratic polynomial f(x) = x2 + x – 2, find the value of 1/α – 1/β.

Solution: 

Given that:

α and β are the roots of the quadratic polynomial f(x) where a = 1, b = 1 and c = – 2

So, we can find

Sum of the roots = α+β = -b/a = – (1)/1 = -1,

Product of the roots = αβ = c/a = -2 /1 = – 2

We have to find, 1/α – 1/β

= [(β – α)/ αβ] = [β-α]/(αβ) x (α-β)/αβ = (√(α+β)2 -4αβ) / αβ = √(1+8) / 2 = 3/2

Question 7. If one of the zero of the quadratic polynomial f(x) = 4x2 – 8kx – 9 is negative of the other, then find the value of k.

Solution: 

Given that,

The quadratic polynomial f(x) where a = 4, b = -8k and c = – 9

And, for roots to be negative of each other, let us assume that the roots α and – α.

Using these values we can find,

Sum of the roots = α – α = -b/a = – (-8k)/1 = 8k = 0 [∵ α – α = 0]

= k = 0

Question 8. If the sum of the zeroes of the quadratic polynomial f(t)=kt2 + 2t + 3k is equal to their product, then find the value of k.

Solution: 

Given that,

The quadratic polynomial f(t)=kt2 + 2t + 3k, where a = k, b = 2 and c = 3k ,

Sum of the roots = Product of the roots



= (-b/a) = (c/a)

= (-2/k) = (3k/k)

= (-2/k) = 3

Hence k = -2/3

Question 9. If α and β are the zeros of the quadratic polynomial p(x) = 4x2 – 5x – 1, find the value of α2 β+α β2

Solution: 

Given that,

α and β are the roots of the quadratic polynomial p(x) where a = 4, b = -5 and c = -1

Using these values we can find,

Sum of the roots = α+β = -b/a = – (-5)/4 = 5/4

Product of the roots = αβ = c/a = -1/4

We have to find, α^2 β+α β^2

= αβ(α +β)

= (-1/4)(5/4) = -5/16

Question 10. If α and β are the zeros of the quadratic polynomial f(t)=t2– 4t + 3, find the value of α4 β33 β4.

Solution: 

Given that,

α and β are the roots of the quadratic polynomial f(t) where a = 1, b = -4 and c = 3

Using these values we can find,

Sum of the roots = α+β = -b/a = – (-4)/1 = 4 ,

Product of the roots = αβ = c/a = 3/1 = 3

We have to find, α4 β3 + α3 β4

= α3 β3 (α +β)

= (αβ)3 (α +β)

= (3)3 (4) = 27 x 4 = 108




My Personal Notes arrow_drop_up
Recommended Articles
Page :